Improving the Energy Efficiency of Ships: Modelling, Simulation, and Optimization of Cost-effective Technologies - Barone, Giovanni; Buonomano, Annamaria; Del Papa, Gianluca; Forzano, Cesare; Francesco Giuzio, Giovanni; Maka, Robert; Palombo, Adolfo; Russo, Giuseppe; Vanoli, Raffaele (Modelling and Optimisation of Ship Energy Systems 2023, 2024)
This paper includes a part of the findings of an international research project, called HEMOS, funded by the EU through the Horizon Europe program, with the aim of decarbonizing the maritime sector. This study focuses on the use of dynamic simulation and optimization to identify policies and technologies for reducing carbon emissions and enhancing the energy efficiency of cruise ships. The primary findings of the study, which sought to identify the ideal ship plant topology, are presented with a particular emphasis on the optimization of the thermal and energy behaviour of a case study cruise ship. By exploiting the developed simulation model and the optimization procedure applied to the Allure of the Seas of the Royal Caribbean Group, potential efficiency measures were identified to enhance the overall efficiency of energy utilization. Several scenarios, including diverse energy efficient user technologies, were analysed and optimized with the aim of providing guidelines for the design of future ships. According to the obtained numerical results, the application of thermal devices for the utilization of on-board waste heat and the implementation of a fuel cell powered by bio-LNG can result in significant primary energy savings of up to approximately 17%, demonstrating that workable solutions to improve the energy efficiency of ships are already available.